Implementation of a Web-Based Theater Show Inventory Borrowing System - Raihan Arief Wicaksana (Jurnal Indonesia Sosial Teknologi, 2025)
Inventory management is one of the important aspects of theatrical performance execution, where several important elements support the needs of the show. Within the scope of Zone 3 Cirebon, there are various theater organizations or groups spread across various campuses. In this study, several campuses were selected as samples: Universitas Muhammadiyah Cirebon (through the "Roempoet" Theater Club), Swadaya Gunungjati University (through USB & "Blue Chain Theater"), UNTAG 17 August (through the Department of Arts and Culture UNTAG 17), and IAIN Syekh Nurjati (through "Teater Awal") in Cirebon. The purpose of this research is to facilitate collaboration between theater organizations from various campuses, thereby facilitating the exchange of information about the borrowing of performance equipment between various organizations in Zone 3 Cirebon. This information system is web-based and developed using hardware such as the HP AMD RYZEN 5 laptop, powered by software including Visual Studio Code and Xampp. It uses the Laravel 8 Framework and the PHP programming language. The final result of this study is the Application of a Web-Based Theater Performance Inventory Borrowing System (Case Study: Campus Theater in Cirebon City). This Information System presents data about inventory, users, inventory types, administrators, loan records, and inventory borrowing and return processes.